Internet of things: Concepts, architectures and technologies - Viel, F.; Silva, A.; Valderi Leithardt; Zeferino, C. (13th IEEE International Conference on Industry Applications, INDUSCON 2018 - Proceedings, 2018)
Internet of Things - IoT - has opened up opportunities for the development of new applications in various segments, being one of the drivers of the revolutions that are occurring in cities and industries. Smart cities and Industry 4.0 represent these revolutions. Given the breadth of concepts and technologies related to IoT, this work seeks to present an overview of these different aspects that support the development of solutions for IoT. In this work, we present a literature review and identify the primary hardware and communication technologies, protocols, algorithms, and security and privacy services for IoT.